Starbo-AFE Compost and Volcanic Ash Improve Coffea liberica Growth in Tropical Peat Soils - Maryani, Anis Tatik; Armando, Yunta Gombang; Aswandi, Aswandi; Sarman, Sarman; Tawakkal, Irfan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Coffee liberica is an economically important yet under-researched coffee species in Indonesia. This study evaluated the individual and combined effects of Starbo-AFE compost and volcanic ash on vegetative growth and physiological performance of C. liberica in Jambi, Indonesia. A two-factor factorial experiment arranged in a randomized complete block design tested three compost rates (0, 250, and 500 g plant⁻¹) and three volcanic ash rates (0, 250, and 500 g plant⁻¹) with three replications. Measured variables included leaf area, primary branch diameter, number of fruiting branches, chlorophyll content, and soil chemical properties. Starbo-AFE compost significantly increased leaf area and branch diameter (p < 0.05), with the highest values at 500 g plant⁻¹, increasing by 54.6% and 17.5%, respectively, compared with the control. Volcanic ash alone showed no short-term effect; however, its combination with compost resulted in the highest chlorophyll content, indicating a synergistic response. Compost improved soil total N and organic carbon, while volcanic ash enhanced potassium availability and potential pH buffering. Overall, applying 500 g Starbo-AFE compost per plant effectively promotes early vegetative growth of C. liberica on peat soils, with volcanic ash contributing to longer-term soil fertility improvement.